2011
DOI: 10.3390/cancers3010267
|View full text |Cite
|
Sign up to set email alerts
|

The Hemostasis Apparatus in Pancreatic Cancer and Its Importance beyond Thrombosis

Abstract: Laboratory evidence of aberrant coagulation is found in the majority of patients with advanced pancreatic cancer and a clinical consequence of this is the high incidence and prevalence of vascular thromboembolic events. Other sequelae are hypothesized to be the facilitation and acceleration of mechanisms that define the malignant phenotype, such as invasion, trafficking and anchoring, establishing the metastatic niche and inducing angiogenesis. We review the in vitro and preclinical evidence that supports the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 114 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…The association between VTE and malignancy was first recognized by Trousseau in 1865. [ 51 ] VTE includes deep vein thrombosis and pulmonary embolism and can significantly affect OS of patients. [ 52 ] Up to now, quite a lot of studies demonstrated the high incidence of VTE in cancer patients, [ 53 55 ] and they have confirmed that VTE was a common complication in malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The association between VTE and malignancy was first recognized by Trousseau in 1865. [ 51 ] VTE includes deep vein thrombosis and pulmonary embolism and can significantly affect OS of patients. [ 52 ] Up to now, quite a lot of studies demonstrated the high incidence of VTE in cancer patients, [ 53 55 ] and they have confirmed that VTE was a common complication in malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of TF is regulated by several factors. The most important is TF pathway inhibitor which is composed of three different domains: the first inhibits FVII, the second inhibits FX and the function of the last one is still unknown (Broze, 1995;Girard et al, 1989;Echrish et al, 2011). TF pathway inhibitor is secreted by endothelial cells.…”
Section: Pathogenesis Of Thrombosis In Pancreatic Cancermentioning
confidence: 99%
“…Proteins of coagulation are involved in angiogenesis in two different ways, one clotting dependent and the other one clotting independent (Echrish et al, 2011). The clotting dependent mechanism is initiated by the activation of TF receptors.…”
Section: Pathogenesis Of Thrombosis In Pancreatic Cancermentioning
confidence: 99%
See 2 more Smart Citations